Colloidal processing of ZnO using thermosensitive poly(N-isopropylacrylamide) as a coagulating agent. Issue 7 (August 2015) - Wang, Xiaofeng; Sun, Yuehua; Peng, Chaoqun; Zhang, Dou; Chen, Yixin; Wang, Richu
Abstract: A novel colloidal processing method is used to prepare near-net-shaped ceramic components directly from suspension. ZnO ceramic components are fabricated using thermosensitive poly(N-isopropylacrylamide) as a coagulation agent. This allows the suspension to consolidate at temperatures above the casting temperature. Low-melting-point paraffin wax is used as the lost mold material. This eliminates the demolding step, through draining at temperatures above the consolidation temperature. The rheology and gelling behavior of the ZnO suspensions is evaluated at different temperatures. A suspension containing 8 mg/mL poly(N-isopropylacrylamide) with a solid loading of 50 vol% is appropriate for casting at low temperature and consolidating at high temperature. Wrinkling and cracking are not observed in the surfaces of the resulting green bodies. The microstructures of the sintered ceramics are homogeneous, and exhibit a density of 97.9% of the theoretical density.